2005
DOI: 10.1080/08860220500200205
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Progressive Renal Failure in Type 2 Diabetes in the Tropical Environment: A Clinico-Pathological Study

Abstract: About two-thirds of patients with type 2 diabetes presenting with rapid decline of renal function in a tropical environment show NDKD. The high incidence of postinfectious glomerulonephritis in this group is possibly related to the high prevalence of skin and soft tissue infections; and could contribute to progressive kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
(17 reference statements)
0
12
0
1
Order By: Relevance
“…12 In a large Italian study of type 2 diabetic patients who underwent renal biopsy, Mazzucco et al 13 found that 70% of cases of PIGN occurred in patients with preexisting diabetic nephropathy. Compared to diabetic patients without renal involvement, patients with diabetic nephropathy are more likely to have advanced end-organ damage, including neuropathy and peripheral vascular disease, 14 and hence are at greater risk for the development of skin ulcers with superimposed bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…12 In a large Italian study of type 2 diabetic patients who underwent renal biopsy, Mazzucco et al 13 found that 70% of cases of PIGN occurred in patients with preexisting diabetic nephropathy. Compared to diabetic patients without renal involvement, patients with diabetic nephropathy are more likely to have advanced end-organ damage, including neuropathy and peripheral vascular disease, 14 and hence are at greater risk for the development of skin ulcers with superimposed bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Information on serum creatinine values was available in 34 studies [6, 7, 9-11, 13, 15-17, 19-21, 23-25, 27-29, 31, 33, 34, 37, 38, 42-48, 50-53]; in 10 of these studies the majority of patients had mean serum creatinine levels falling roughly within the normal range (<1.43 mg/dL) [16, 20, 25, 28, 31, 42-44, 51, 52]. In 12 studies mean values ranged from 1.44 to 3.00 mg/dL [7,10,13,23,25,27,29,34,37,45,47,53] while the remaining 12 included patients with quite severely compromised renal function (serum creatinine >3 mg/dL) [6,9,11,12,15,19,21,24,33,38,46,50]. Data on estimated glomerular filtration rate (eGFR) were available in 16 of the above-mentioned studies reporting information on serum creatinine [7, 10, 13, 15-17, 19-21, 28, 34, 42, 48, 51-53].…”
Section: Study and Participants' Characteristicsmentioning
confidence: 99%
“…Existe otra serie de estudios que se han focalizado en ERND, pero con una población de pacientes básicamente macroalbuminúricos, o con síndrome nefrótico, en quienes el hallazgo predominante fue la glomeruloesclerosis focal segmental y ND [23][24][25] . En otras situaciones, se han analizado pacientes diabéticos con deterioro renal rápidamente progresivo, resaltándose, en ellos, glomerulonefritis postinfecciosa, glomerulonefritis rápidamente progresiva y nefritis intersticial aguda 26,27 . Hay pocos trabajos que se hayan centralizado en una población semejante a la que nosotros estudiamos: principalmente ancianos diabéticos, con baja tasa de filtración glomerular y no macroalbuminuria.…”
Section: Discussionunclassified